Intraoperative consultation and smear cytology in the diagnosis of brain tumours - Kini, JR; Jeyraj, V; Jayaprakash, CS; Indira, S; Naik, CNR (Kathmandu University Medical Journal, 2009)
Background: Intraoperative smear cytology provides a rapid and reliable intraoperative diagnosis and guidance to the neurosurgeon during surgical resection and lesion targeting. It also helps the surgeon to monitor and modify the approach at surgery. Objectives: 1) To assess the utility of intraoperative smear cytology and correlate with the final histopathological diagnosis. 2) To describe the cytomorphological features of common brain tumours in smear preparation. Materials and methods: The material for this study was obtained from 100 consecutive biopsies of central nervous system neoplasms sent for intraoperative consultation. Smears were prepared from the biopsy samples sent in isotonic saline for immediate processing. The smears were stained by the rapid Haematoxylin and Eosin method. The cytomorphological features were noted and correlated with paraffin section findings. Results: Of the total 100 cases, 86 showed accuracy when compared with histopathological diagnosis. This was comparable with other studies. Of the remaining, two cases were frank errors, 12 cases showed partial correlation, with five cases showed incomplete typing of the cell type and seven, discrepancy in grading of tumours. The error percentage was 14%. Correlation with clinical details and radiological findings were helpful in improving the accuracy rate. Conclusions: Smear technique is a fairly accurate, relatively safe, rapid, simple, easily reproducible and cost effective tool to diagnose brain tumours. Smear cytology is of great value in intraoperative consultation of central nervous system pathology. Key words: Intraoperative consultation, smear cytology, central nervous system neoplasms doi: 10.3126/kumj.v6i4.1734 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 453-457